I would surely like to know your approach

Algebra Level 4

8 x + 2 7 x 1 2 x + 1 8 x = 7 6 \dfrac {8^{x}+27^{x}}{12^{x}+18^{x}}=\dfrac {7}{6}

Find the product of all real values of x x satisfying the above equation .


The answer is -1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rohit Udaiwal
Nov 5, 2015

Let 2 x 2^x be a a and 3 x 3^x be b b .Therefore 8 x = a 3 8^x=a^3 and 2 7 x = b 3 27^x=b^3

1 2 x = ( 2 2 × 3 ) x = ( 2 x ) 2 . 3 x = a 2 b similarly 1 8 x = a b 2 12^x=(2^2×3)^{x}=(2^{x})^{2}.3^{x}=a^{2}b~~ \text {similarly }18^{x}=ab^{2} The equation becomes a 3 + b 3 a b ( a + b ) = 7 6 \dfrac {a^3+b^3}{ab (a+b)}=\dfrac{7}{6} As a 3 + b 3 = ( a + b ) ( a 2 + b 2 a b ) a^3+b^3=(a+b)(a^2+b^2-ab) 6 ( a 2 + b 2 a b ) = 7 a b 6 a 2 13 a b + 6 b 2 = 0 6 (a^2+b^2-ab)=7ab \\ \implies 6a^2-13ab+6b^2=0 Divide throughout by b 2 b^2 6 ( a b ) 2 13 ( a b ) + 6 = 0 \implies 6 \left (\dfrac {a}{b}\right)^{2}-13\left (\dfrac {a}{b}\right)+6=0 The equation becomes a quadratic in ( a b ) \left (\dfrac {a}{b}\right) .Solving for ( a b ) \left (\dfrac {a}{b}\right) ,we get ( a b ) = 2 3 , 3 2 ( 2 3 ) x = 2 3 or 3 2 x = ± 1 \left (\dfrac{a}{b}\right)=\dfrac{2}{3},\dfrac {3}{2}\\ \implies \left (\dfrac {2}{3}\right)^ {x}=\dfrac {2}{3} \text {or} \dfrac {3}{2} \\ \boxed {\therefore x=\pm 1}

Same solution

Vishal S - 5 years, 7 months ago
Otto Bretscher
Nov 5, 2015

Canceling out 2 x + 3 x 2^x+3^x , we can write the given equation as 4 x 6 x + 9 x 6 x = ( 2 3 ) x 1 + ( 3 2 ) x = 7 6 \frac{4^x-6^x+9^x}{6^x}=\left(\frac{2}{3}\right)^x-1+\left(\frac{3}{2}\right)^x=\frac{7}{6} and, after multiplying with ( 2 3 ) x \left(\frac{2}{3}\right)^x , ( ( 2 3 ) x 2 3 ) ( ( 2 3 ) x 3 2 ) = 0 \left(\left(\frac{2}{3}\right)^x-\frac{2}{3}\right)\left(\left(\frac{2}{3}\right)^x-\frac{3}{2}\right)=0 The solutions are x = 1 , 1 x=1,-1 , with their product being 1 \boxed{-1} .

Moderator note:

Nice observation of the factorization to find the solutions to the equation :)

Oh no, I forgot about the -1. Thanks for the solution

Debmeet Banerjee - 5 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...